SCJ 579: Racial and Ethnic Relations - Offiong, Daniel (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
The aim of this course is to introduce students to the specific issues in the area of race and ethnicity with emphasis on the pervasive nature of differential treatment in America and around the globe. It further seeks to bring to the student a comprehensive understanding of the theories and concepts of inter-group relations, including sociological, economic, political, and psychological insights. By studying racial and ethnic groups, with their experiences placed in a socio-historical perspective, the student will come to understand the present through familiarity with past patterns of majority-minority relations and to see the relationships between anyone group’s experiences and all others.